SIAPA ITU WISATAWAN? MEMAKNAI PERKEMBANGAN KONSEPTUAL DAN PRAKTIS DALAM STUDI PARIWISATA - Putu Diah Sastri Pitanatri; Made Uttari Pitanatri (JURNAL KEPARIWISATAAN, 2021)
In early 2020, the terminology of who is a tourist has become a debate again when the Covid-19 pandemic broke out. The question arises whether the locals "deserve" the title "tourists"? Whether they are included in the category of domestic tourists? Are they categorized as tourist? With the rapid development of the understanding of this terminology, several questions have arisen that have led to the calculation of the number and distribution of tourists in travel destinations. Therefore, this work aims to unravel the tangled threads using the basic conceptual approach of tourism terminology. The literature study method is carried out by bibliometric examination. Hopefully this article provides a clearer construction to reduce confusion over the use of the term "tourist".